Digital connection, real bonding: Brief online chats boost interpersonal closeness regardless of the conversational topic - Chiara Fini; Vanessa Era; Giovanna Cuomo; Ilenia Falcinelli; Mattia A. Gervasi; Matteo Candidi; Claudia Mazzuca; Marco Tullio Liuzza; Bodo Winter; Anna M. Borghi (Heliyon)
This study explores how the quality of brief dyadic written exchanges (lasting under 5 min) on a virtual platform and the nature of the conversational topic (abstract or concrete), influences physical, interpersonal, and psychological closeness between interlocutors. In the first experiment, participants engaged in written conversations on either an abstract or concrete topic under two conditions: (i) an interactive condition, where participants exchanged messages with another person, and (ii) a non-interactive condition, where participants wrote independently on the same topic, aware that another person was simultaneously doing the same. Results indicated that participants in the interactive condition reported feeling significantly closer to their interlocutor than those in the non-interactive condition. In addition, greater perceived pleasantness, intimacy, and the importance of the other person's contribution to the conversation were associated with increased feelings of closeness. However, inconclusive evidence was obtained regarding the interaction of the other person's contribution with the abstractness of the conversational topic during the written exchanges in fostering feelings of closeness. The second experiment focused only on the interactive condition, where we examined interpersonal dynamics across different subcategories of abstract (e.g., philosophical/spiritual, emotional, social, physical/spatio-temporal) and concrete topics (e.g., tools, animals, food). The results of the first experiment were replicated, reinforcing the idea that the quality of the virtual exchange—rather than the topic itself—plays a crucial role in fostering feelings of closeness between individuals.